Ways of knowing climate: Hubert H. Lamb and climate research in the UK. (14th July 2015) - Martin‐Nielsen, Janet
Abstract : Today, numerical modelling is widely seen as the leading method of climate research. Modelling enjoys a hegemonic status in the production of climate predictions and the discussion and policy application of climate knowledge. This dominance obscures past and present debates about which types of climate knowledge are important, which epistemic standards are used to judge that knowledge, and which applications of that knowledge are considered useful. In the existing historiography of climate research, the focus has overwhelmingly been on numerical modelling, and relatively little has been written about other ways of knowing climate. The hegemony that numerical models enjoy today is not the result of a linear 'arrow of progress, ' beginning with the introduction of digital computers and leading naturally to today's situation, but rather of a more complex situation centered on changing ideas of climate, the identity of climate researchers, and the direction and scope of their work. This paper aims to shed light on these ideas by investigating and analyzing climate research debates in the 1960s and early 1970s through the lens of the English meteorologist and climatologist Hubert Horace Lamb (1913–1997). It pays particular attention to Lamb's understanding of climatology as a discipline and his assessment of that discipline through the latter half of the 20 th century. WIREs Clim Change 2015, 6:465–477. doi: 10.1002/wcc.349 This article is categorized under: Climate, History, Society, Culture > Thought Leaders